CAUSES AND CONSEQUENCES OF THE SCHOOL IN HIGH SCHOOL DROPOUT: CASE UNIVERSIDAD AUTÓNOMA DE SINALOA - Ramírez, Rosalva Ruiz (Universidad Autónoma Indígena de México, 2018)
The present investigation has the objective to establish the personal, economic and social causes and consequences that create school desertion of high school in Universidad Autónoma de Sinaloa (UAS). The investigation took place in the high school located in the municipality of El Fuerte, Sinaloa, in the academic unit (UA) of San Blas and its extensions The Constancia and The Higueras of the Natoches in 2013. A mixed approach was used to analyze qualitative and quantitative information; the studied population was 18 women and 17 men deserters of the school cycle 2011-2012, ten teachers, four directors and twenty non-deserting students. In the results one can see that the principal factor for school desertion was the personnel to be married and not approving classes. The main consequence was economic, highlighting that the poverty cycle is hard to break.